2014
DOI: 10.1186/s13059-014-0423-1
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of chromosomal regulatory boundaries are associated with congenital disease

Abstract: BackgroundRecent data from genome-wide chromosome conformation capture analysis indicate that the human genome is divided into conserved megabase-sized self-interacting regions called topological domains. These topological domains form the regulatory backbone of the genome and are separated by regulatory boundary elements or barriers. Copy-number variations can potentially alter the topological domain architecture by deleting or duplicating the barriers and thereby allowing enhancers from neighboring domains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 67 publications
9
137
0
1
Order By: Relevance
“…Despite multiple studies, the mechanisms underlying the formation of topological domain boundaries remain unknown. It has been previously suggested that genomic deletions at TAD boundaries in normal cells result in a change in local chromatin organization and in a formation of new domain boundaries (Nora et al 2012;Ibn-Salem et al 2014). We therefore investigated the role of genomic sequence variation in establishing TAD boundaries in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple studies, the mechanisms underlying the formation of topological domain boundaries remain unknown. It has been previously suggested that genomic deletions at TAD boundaries in normal cells result in a change in local chromatin organization and in a formation of new domain boundaries (Nora et al 2012;Ibn-Salem et al 2014). We therefore investigated the role of genomic sequence variation in establishing TAD boundaries in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This genomic mechanism is not necessarily limited to these disorders. Recently, losses of cis -regulatory elements, imbalance in coding and noncoding elements, illegitimate adoption of enhancer sequences and the like, resulting from CNVs have been proposed as a general mechanism of 'genomic' disease [Klopocki and Mundlos, 2011;Lettice et al, 2011;Poot and Kas, 2013;Spielmann and Klopocki, 2013;Gordon et al, 2014;Ibn-Salem et al, 2014;Lupiáñez et al, 2015]. CNVs may also cause 'side effects', i.e.…”
Section: Mechanisms Based On Disruption Of the Genomic Architecturementioning
confidence: 99%
“…Next, the phenotypes of model organisms with disruptions of the orthologous genes, and features of breakpoint regions of the human CCRs, such as LINE elements, segmental duplications, 'side effects' on transcription levels of genes in the vicinity of the breakpoints, markers of active promoters (e.g. H3K4Me1, H3K27Ac), and adoption of enhancers or insulators have to be taken into consideration [Reymond et al, 2007;Hehir-Kwa et al, 2010;Spielmann and Mundlos, 2013;Ibn-Salem et al, 2014]. All these sophisticated methods of bioinformatic predictions notwithstanding, experimental confirmation of gene disruption or alteration of mRNA levels in a phenotypically relevant tissue of the patient remains necessary [Kloosterman and Hochstenbach, 2014].…”
Section: Multiple Possibly Pathogenic Mechanisms Provoked By Ccrs: Twmentioning
confidence: 99%
“…Furthermore, replication programs and organization of chromosomes into TADs appear to be reestablished simultaneously after mitosis (Dileep et al 2015a). Finally, disruption of TADs, in particular fusion of the neighboring TADs, results in dramatic changes of promoter-enhancer interactions and may cause various diseases (Ibn-Salem et al 2014;Ji et al 2016;Lupianez et al 2015Lupianez et al , 2016Petrov et al 2006Petrov et al , 2008. Thus, organization of the genome into spatial domains is directly related to the functioning of the genome (Pombo and Dillon 2015;Sexton and Cavalli 2015).…”
Section: Linear or Three-dimensional?mentioning
confidence: 99%